Bilateral Presidency in Al-Mashriq Church before Islam A Study in the Situation of the Iraqi Church during the Era of Schism and Chaos (523-539 A.D) - Abbas, Othman Fadhel (Journal of Tikrit University for Humanities, 2022)
This study deals with the events of the division and the dual leadership in Al-Mashriq Syriac Church during the period between (523-539 AD) and the competition between the Catholicos Narsai and Elisha for the presideny. It also deals with the most prominent developments that Al-Mashriq Church experienced during that time, as it faced a major problem as a result of the division happened among the Christian clergy themselves in the support of one of the Catholics. Personal interests played a role in fueling the events of this conflict, and the conflict remained until Narsai died and Elisha attempted to seize the presidency, but the intervention of the Sassanid state represented by King Khosrau Anushirwan prevented this from happening. As Elisha was isolated due to his bad conduct with the Christians and the isolation of his group Paul was ordained with the support of King Khosrau Anushirwan, and the dual presidency ended and the unity of the church was restored. Hence, the effects of the conflict remained due to the short period of Paul’s presidency, and the period of the dual presidency was about fifteen years long. The Catholic Mar Abba the Great came and removed the traces of the dual presidency.